GE_GERICHTE P/15524/2013 vom 1. Dezember 2014 - GE Cour de justice (2014)
PRÉSOMPTION D'INNOCENCE; IN DUBIO PRO REO; DROIT DES ÉTRANGERS; RENSEIGNEMENT ERRONÉ; ERREUR DE DROIT(DROIT PÉNAL); CONFISCATION(DROIT PÉNAL) | LEtr.118.1; CP.21; CP.69